Fracture behavior of a melt-infiltration-processed SiC/Si composite at 900 °C in argon, air, and steam. Issue 2 (February 2023) - Scofield, Gregory D.; Hwang, Sunghwan; Caccia, Mario; Chamberlain, Adam L.; Kush, Matthew T.; Sangid, Michael D.; Sandhage, Kenneth H.
Abstract: The fracture behavior of a melt-infiltration-processed SiC/Si composite, used to mimic the matrices of industrial fiber-reinforced ceramic composites, was examined in different atmospheres and temperatures. Specimens tested in four-point bending at 900 °C in oxygen-gettered argon, dry air, or steam-rich atmospheres exhibited higher average fracture strengths than specimens tested at 25 °C. Higher mean fracture strength values were obtained for specimens tested in dry air or in a steam-rich atmosphere at 900 °C than for specimens tested in high-purity, oxygen-gettered argon at this temperature. The increased fracture strengths obtained in air and in steam-rich atmospheres coincided with increased specimen oxidation and apparent oxide filling and blunting of flaws in these composites. A transition in the location of catastrophic failure, from sites of preexisting damage created by Vickers indentations for tests in argon to other locations for tests in air or steam-rich atmospheres, was also consistent with such apparent oxide filling/blunting of indentation-induced flaws.